2013
DOI: 10.1038/ki.2013.48
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Notch1-dependent effects on glomerular parietal epithelial cells promotes collapsing focal segmental glomerulosclerosis with progressive podocyte loss

Abstract: Collapsing focal segmental glomerulosclerosis (cFSGS) is a progressive kidney disease characterized by glomerular collapse with epithelial hyperplasia. Here we used a transgenic mouse model of cFSGS with immunotoxin-induced podocyte-specific injury to determine the role for Notch signaling in its pathogenesis. The mice exhibited progressive loss of podocytes and severe proteinuria concomitant with histological features of cFSGS. Hyperplastic epithelium was negative for genetic podocyte tags, but positive for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 43 publications
2
48
0
Order By: Relevance
“…Other potential therapeutic targets for PECs in disease might include epidermal growth factor [48] and its receptor [49], as well as the amino acid transporter LAT2 [50]. More recently, Ueno et al [51] showed that inhibiting Notch in vivo in experimental collapsing FSGS reduced the expression of mesenchymal-like markers including alpha smooth muscle actin, vimentin, and snail.…”
Section: Parietal Epithelial Cells As a Potential Therapeutic Target mentioning
confidence: 99%
“…Other potential therapeutic targets for PECs in disease might include epidermal growth factor [48] and its receptor [49], as well as the amino acid transporter LAT2 [50]. More recently, Ueno et al [51] showed that inhibiting Notch in vivo in experimental collapsing FSGS reduced the expression of mesenchymal-like markers including alpha smooth muscle actin, vimentin, and snail.…”
Section: Parietal Epithelial Cells As a Potential Therapeutic Target mentioning
confidence: 99%
“…Accordingly, inhibition of Notch signaling throughout the regenerative phases led to aggravation of the albuminuria and glomerulosclerosis in a murine model of Adriamycin nephropathy [15]. Furthermore, prolonged Notch blocking in a genetically engineered mouse model of FSGS reduced RPC proliferation and the formation of RPC hyperplastic lesions but worsened podocyte loss and proteinuria [16]. Therefore, a tight regulation of the Notch pathway compensates for a disrupted GFB with progressive podocyte loss.…”
Section: When Regeneration Work: Successful Renal Progenitor Cell DImentioning
confidence: 99%
“…51 Isolated glomeruli were lysed in 0.5% CHAPS buffer. Samples were resolved on SDS-polyacrylamide gels.…”
Section: Western Blottingmentioning
confidence: 99%